MORPHOLOGICAL FEATURES OF OFFICIAL-BUSINESS STYLE - Ryadinskaya, A.I. (PUBLISHINGS of Kostanay State Pedagogical University, 2020)
This article describes the grammar features of the official-business style. The goal of this article is to analyze morphological and syntax aspects of official-business style and to identify the features of practical implementation in the documentation. The text gives valuable information about the specific features of the official-business style – the differences between morphological and syntax aspects of sub styles. Much attention is given the grammar mistakes and ways of disposal.
Keywords: the official-business style; morphology; syntax; documentation